Leveraging Community Health Workers as a Novel Approach to Reduce Maternal Mortality: A Discourse Analysis - Awobode, Janet; Ansie, Vera (Yayasan Ilomata, 2024)
Maternal mortality remains unacceptably high, particularly in low and middle-income countries (LMICs), representing a critical challenge requiring novel approaches to reach underserved populations. Community health worker (CHW) programs have demonstrated potential to promote maternal health by enhancing health literacy, service utilization, and access to care. This study aimed to critically synthesize evidence on leveraging CHWs as an innovative strategy for reducing maternal deaths across LMICs. A review of empirical literature from 2000-2023 was conducted across major databases (PubMed, CINAHL, Embase). Quantitative, qualitative, mixed-methods and review studies reporting primary data on CHW program impacts related to maternal health in LMICs were included. Thematic synthesis was used to explore CHW roles, implementation factors affecting effectiveness, and impacts on drivers of maternal mortality. CHWs increased antenatal care attendance, facility-based deliveries, obstetric complication recognition/referrals, and postnatal follow-up—contributing to reductions in maternal mortality across contexts like Nepal, Ethiopia, and Malawi. However, optimizing impact required comprehensive training, logistical support, functional integration of CHWs into health systems, community participation mechanisms, and tailored incentive packages fostering motivation. Persistent implementation challenges included poor supervision, lack of supplies/transportation, fragmented referral coordination, and inadequate sustainable financing. On implications, there is the need for context-adapted program models underpinned by health system readiness and multistakeholder commitment to overcoming long-standing implementation barriers.